2009
DOI: 10.1900/rds.2009.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Monophosphate-Activated Protein Kinase (AMPK) as a New Target for Antidiabetic Drugs: A Review on Metabolic, Pharmacological and Chemical Considerations

Abstract: ■ AbstractIn view of the epidemic nature of type 2 diabetes and the substantial rate of failure of current oral antidiabetic drugs the quest for new therapeutics is intensive. The adenosine monophosphate-activated protein kinase (AMPK) is an important regulatory protein for cellular energy balance and is considered a master switch of glucose and lipid metabolism in various organs, especially in skeletal muscle and liver. In skeletal muscles, AMPK stimulates glucose transport and fatty acid oxidation. In the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 191 publications
(176 reference statements)
3
83
0
3
Order By: Relevance
“…19) But the enhancement effect by quercetin in our work are weaker (by about 20%, data not shown), it may results from the dose we used (5, 10, 20 µm) is lower than eid et al (100 µm). As the activation of muscle AMPK by exogenous compounds recruits GlUT4 and augments the rate of glucose transport independent of insulin, 27) we suppose that quercetin may also stimulate GLUT4 to promote glucose uptake in C2C12 myotubes, and we have verified it in other works (data not shown). Also, previous studies have demonstrated that quercetin could increase GLUT4 in both ob/ob mice and skeletal muscle myotubes.…”
Section: Discussionsupporting
confidence: 72%
“…19) But the enhancement effect by quercetin in our work are weaker (by about 20%, data not shown), it may results from the dose we used (5, 10, 20 µm) is lower than eid et al (100 µm). As the activation of muscle AMPK by exogenous compounds recruits GlUT4 and augments the rate of glucose transport independent of insulin, 27) we suppose that quercetin may also stimulate GLUT4 to promote glucose uptake in C2C12 myotubes, and we have verified it in other works (data not shown). Also, previous studies have demonstrated that quercetin could increase GLUT4 in both ob/ob mice and skeletal muscle myotubes.…”
Section: Discussionsupporting
confidence: 72%
“…The central significance of AMPK as a metabolic regulator makes it an attractive potential target for drug action in diseases of positive malnutrition (5,14,48). Efforts are in hand to evolve prototypical activators into safe and effective drugs (49 -51).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work established the essential role of AMPK in the regulation of carbohydrate, protein and lipid metabolism; this made AMPK a key target for the treatment of type 2 diabetes, obesity and metabolic syndrome (Gruzman, Babai & Sasson, 2009;Hardie, 2008b;Steinberg & Kemp, 2009;Viollet et al, 2010;Viollet et al, 2009b). Indeed, in a clinical setting AMPK activity is altered with the anti-diabetic drug metformin and other biguanides.…”
Section: Pharmacological Compounds and Other Factors That Alter Ampk mentioning
confidence: 99%
“…Pharmacological drugs have also been critical to define how AMPK mediates metabolic control (see Table 1). These compounds employ a variety of molecular mechanisms that culminate in AMPK activation (Gruzman et al, 2009;Hawley et al, 2010;Mantovani & Roy, 2011). For example, the kinase can be activated by a rise in the AMP/ATP ratio, generation of an AMP mimetic or increase in intracellular Ca 2+ concentrations (Hawley et al, 2010).…”
Section: Pharmacological Compounds and Other Factors That Alter Ampk mentioning
confidence: 99%
See 1 more Smart Citation